Technological features of distribution between river basins using GIS technologies (based on the example of r. Brusnytsya) - Bespalko, Ruslan; Hutsul, Taras (Вісник Харківського національного університету імені В.Н. Каразіна. Серія Геологія. Географія. Екологія, 2021)
Formulation of the problem. The catchment area and surface runoff volume – morphometric parameters calculated from digital terrain models – are widely used in geographic information analysis of the area. They are attributed to the block of hydrological parameters, where they are basic concepts. The emergence and widespread usage of GIS tools has greatly simplified this labor-intensive process. However, the complexity of the applied algorithms forms the sensitivity of the models to the entered parameters, the values of most of which are selected by the user through numerous attempts and tests. The research methodology. The study examines the most common GIS tools from many existing ones that support hydrology tools – ArcGIS, Global Mapper, SAGA GIS, Surfer. Finding out the principles of operation of hydrological tools in different GIS environments and the applied algorithms was one of the goals, the solution of which was revealed in the process of research methodology. The same set of initial data obtained as a result of vectorization of relief elements of a fragment of a topographic map of the research territory is used for all software. The digital terrain model was prepared taking into account the requirements and features of hydrologically correct models. The initial data were checked for topological correctness. In order to determine the influence of separate DEM on the results of the boundaries, its modeling was performed in three versions – 10 × 10 m; 25 × 25 m; 50 × 50 m. According to the same algorithm in each of the GIS tools, the boundaries of the basins were selected. The obtained map metrics were entered into comparative tables, and in some cases were subject to correlation analysis. As a result of studies. The correct location and accurate plotting of the catchment areas of water bodies on the cartographic material has a decisive influence on the accuracy of determining their areas. No direct relationship was found between the effect of the DEM resolution on the results of modeling the boundaries of catchment areas. However, the resolution of the DEM affects the detail of the hydrographic network. It is established that for the same parameter ( ), there is a linear relationship between the cell size and the total length of the river network within the studied basins. Despite the study of hydrological modeling algorithms used in GIS tools, the most difficult is the special sensitivity of the models to the entered parameters. A correlation (very high level of connection) has been established, which consists in reducing the length and number of selected objects of watercourses with increasing the threshold value of the amount of runoff ( ). The scientific novelty. The obtained results are aimed at increasing the accuracy of modeling the boundaries of catchment basins and calculating the derived hydrographic parameters. They can be used to generalize hydrographic network objects within dedicated catchments and to achieve a reasonable degree of cartographic compliance and detail depending on the objectives and scope of research. The practical significance. Thus, both the resolution of the DEM and the value of the runoff threshold have a direct impact on the derived hydrographic parameters (for example, the density of the river network).